Oviposition preference assessment of Diabrotica speciosa (Coleoptera: Chrysomelidae) for different soybean genotypes - Costa, Eduardo Neves [UNESP]; Ribeiro, Zulene Antonio [UNESP]; Sardinha de Souza, Bruno Henrique [UNESP]; Boica Junior, Arlindo Leal [UNESP] (Taylor & Francis Ltd, 2014)
This study assessed current research methods and applied them to tests of oviposition preference by Diabrotica speciosa (Germar) for different soybean genotypes; the correlation between the number of eggs per plant and leaf intake was evaluated. The experiments were divided into four parts: (i) assessing the preferred oviposition substrate; (ii) standardizing the number of D.speciosa pairs, (iii) evaluating the preferred soybean plant age, and (iv) testing the preference for oviposition on different soybean genotypes, and evaluating its correlation with leaf intake under laboratory conditions. Females of D.speciosa preferred to lay eggs in the soil, with the highest number of eggs laid in the presence of a growing soybean plant. The genotypes PI 227687, DM 339, and PI 274454 were the least preferred varieties for oviposition, while BRSGO 8360 was the most preferred genotype. Egg counts were not correlated with leaf intake, except for the variety IGRA RA 626 RR, which showed positive correlation. Our discoveries may be helpful for second-crop use of resistant genotypes in areas where different crops are cultivated, by reducing the pest density off-season.
Keywords: soil pests; Host plant resistance; antixenosis; Pest management; corn rootworm; Glycine max; oviposition behavior; leaf beetle